Implementation of Information and Communication Technology on Reading Ability of Students in Higher Education - Manurung, Paisal; Harahap, Dian Anggraini; Ansi, Rahma Yunita; Sambayu, Harry (Universitas Negeri Makassar, 2021)
This article discusses the implementation of information and communication technology on the reading ability of students in tertiary institutions. The method for collecting data sources uses quantitative descriptive methods. This method presents data and describes data based on books, journals, and several other sources. This article examines and presents information and communication technology in the reading ability of students in tertiary institutions, including input competency for higher education is very necessary, as a form of higher education readiness in maintaining graduate quality. Curriculum development in tertiary institutions should continue to be reconstructed against changes that occur, especially the ability to receive information and disseminate it to the public. Interest in reading and ICT will be achieved in national education standards in Indonesia, which will be a solution to the problem of information delays and will continue to be minimized.